KINESIOLOGI YOGA ASANAS (KUNCI KEBAHAGIAAN TUBUH, PIKIRAN DAN JIWA) - Sena, I Gusti Made Widya (Institut Hindu Dharma Negeri Denpasar, 2018)
Yoga means the experience of wholeness or unity with the inner being. This unity comes after destroying the duality of the mind into the highest consciousness. Asana, pranayama, mudra and bandha are the four major studies of yoga. The four elements can not be separated, interconnected and related to each other. Asanas is the third step in eight stages of yoga path, known as astangga yoga or eight stages of yoga. The goal is to make our body steady and ready for higher techniques such as pranayama (breath setting), pratyahara (sensual withdrawal), dharana (concentration), dhyana (meditation) and Samadhi (cosmic realization). In addition the asanas movement makes the production of hormones from different glands to be balanced, the position of stretch and bend of the movement of asanas, which is done within a certain time, put special pressure and sustained on the glands that will stimulate the gland in various ways, regulate the production of glands and will eventually control the emotions. If the gland deficiency is resolved, the mind becomes free from emotional disturbances and perfect inner calm will be achieved. Kinesiology is a reference theory that deals with motion in terms of analyzing the work function of muscles for and after performing yoga asanas movements on the human body.